Global South Free Culture Meeting: the Community Cultural Production in the Commons’ Construction - Martins, Beatriz Cintra (2020)
DOI: 10.26439/contratexto2020.n033.4786 In this article, we intend to systematize the networking experience for the Global South Free Culture Meeting, based on the collective construction of the first meeting, entirely virtual, held in 2018. As a method for our reflection, we used the content analysis of the thematic tables, recorded in videos, and participant observation. In our theoretical approach, we bring the debate around the construction of commons and the problematization of the free term in the current political and social context of Latin America, seeking to articulate it with the concept of community cultural production. Then, we present a summary of the process of construction of the Meeting and also of the topics discussed at the event, recording the planning for its continuity. Finally, we believe that the meeting favored the strengthening of the free culture movement in the Global South, which presents itself as an alternative for the construction of common cultural assets based on the differences and peculiarities of these territoriesand contributes to mitigate their inequalities.